My question is how should I use propositional logic rules for → and ↔ (although other rules may be required) to prove the following:

  1. A → B, B → C ⊢ (AvB) → C

  2. A ↔ B ⊢ ¬A ↔ ¬B

Please use the language of propositional logic.


Here's an answer to your first question using conditional proof. If you're unfamiliar with it, conditional proof is a proof method in PL that allows you to assume the antecedent of a conclusion (assuming, of course, that the main operator of your conclusion is a conditional), and allows you to derive a conditional whose consequent is whatever you can deduce within the scope of your assumption. This is what's going on on lines 4-6. Notice the indentation - by convention, we indent whatever follows from our assumption, only returning to the non-indented position when we discharge our assumption by deriving the conditional (again, a conditional whose antecedent == whatever you've assumed).

enter image description here

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.